2005
DOI: 10.1093/ecam/neh087
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Psychological Benefits of Aromatherapy Massage

Abstract: This preliminary investigation compares peripheral blood cell counts including red blood cells (RBCs), white blood cells (WBCs), neutrophils, peripheral blood lymphocytes (PBLs), CD4+, CD8+ and CD16+ lymphocytes, CD4+/CD8+ ratio, hematocrit, humoral parameters including serum interferon-γ and interleukin-6, salivary secretory immunoglobulin A (IgA). Psychological measures including the State–Trait Anxiety Inventory (STAI) questionnaire and the Self-rating Depression Scale (SDS) between recipients (n = 11) of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 24 publications
5
53
2
3
Order By: Relevance
“…Using the adjusted post-assessment values, the lymphocyte count was 11.4% higher in the treatment group than in the controls. This outcome is consistent with the findings reported by Hernandez-Rief et al (2004;2005), Kuriyama et al (2005) and Imanishi et al (2009) that massage (and, in particular, aromatherapy massage) can boost lymphocyte numbers. It is potentially very important, especially in terms of the apparent effect size, to cancer patients if an improvement in their immune system functioning can help to protect them from infections during the course of their chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Using the adjusted post-assessment values, the lymphocyte count was 11.4% higher in the treatment group than in the controls. This outcome is consistent with the findings reported by Hernandez-Rief et al (2004;2005), Kuriyama et al (2005) and Imanishi et al (2009) that massage (and, in particular, aromatherapy massage) can boost lymphocyte numbers. It is potentially very important, especially in terms of the apparent effect size, to cancer patients if an improvement in their immune system functioning can help to protect them from infections during the course of their chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…It is potentially very important, especially in terms of the apparent effect size, to cancer patients if an improvement in their immune system functioning can help to protect them from infections during the course of their chemotherapy. However, in contrast to other studies, no significant differences were found for WBCs in general or in the other measures of immune system functioning involving various specific different types of WBCs: for example, Field et al (2001) found that massage increased WBCs and neutrophils, Diego et al (2001) reported that it increased CD4 cells and the CD4/CD8 ratio, and Kuriyama et al (2005) found that it increased the CD8 cell count. Differences between the results of the present and other studies may be explained in terms of differences in the populations studied, in the frequency, length, spacing and number of massage sessions, and in the massage procedure itself.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Some essential oils applied via respiration and orally were also reported to reduce the symptoms and strengthen the memory in neurodegenerative diseases like Alzheimer (7,14). In this work, different effects were observed in the studied age groups.…”
Section: Rose Oilmentioning
confidence: 64%
“…Lavender is a safe herb and no toxicity has been reported (Cavanagh & Wilkinson, 2002). Aromatherapy massage combines the positive effects of massage and aromatherapy, resulting in a complementary therapy that is more effective than either method alone (Kuriyama et al, 2005). As a treatment, aromatherapy massage focuses on controlling symptoms.…”
Section: Introductionmentioning
confidence: 99%